An RGB image encryption using diffusion process associated with chaotic map. (April 2015) - Kumar, Manish; Powduri, Pradeep; Reddy, Avinash
Abstract: Image encryption and decryption are essential for securing images from various types of security attacks. In this paper, we have proposed a new algorithm for RGB image encryption and decryption using diffusion method with a combination of chaotic maps. We have formulated a new algorithm for the entire possible range to choose keys for encrypting and decrypting RGB image. Computer simulation with two standard examples and results are given to analyse the capability of the proposed approach. Several important analysis like key space, key sensitivity, NPCR, UACI, MSE and PSNR analysis are performed. Results of various analysis and computer simulation confirm that the new algorithm offers high security and is suitable for practical image encryption.